ANALISIS PERKEMBANGAN KARAKTER DI ERA DIGITAL BAGI ANAK SEKOLAH DASAR - Yesika Siburian, Vina Sihotang, Fiber Yun Almanda Ginting (CV. ADIBA AISHA AMIRA, 2024)
Character education in the digital era is an important topic to study. The digital era presents various opportunities and challenges in instilling character values ​​in elementary school children. This research aims to understand the characteristics of elementary school children in the digital era, the goals of character education, basic concepts of character education, principles of character education, and strengthening character education in digital literacy learning. This research uses a descriptive-qualitative method with a literature study approach. Data is collected through journals, proceedings, e-books, theses and other scientific works relevant to the object of study. The research results of the characteristics of elementary school children in the digital era show several things, namely: Lack of social interaction and traditional play, Responsibilities that have not been optimally formed, Tendency to play social media and online games. The aim of character education in the digital era is to: Create Indonesia's golden generation 2045, Develop the abilities and capacity of researchers, education staff, students, communities and families, Form good character to face the dynamics of future change. Character education for elementary school children in the digital era has unique challenges and opportunities. The challenge is how to instill character values ​​in children amidst the onslaught of digital technology. The opportunity is that digital technology can be used to support character education. Strengthening character education in digital literacy learning is the key to creating an advanced, intelligent and noble generation.